Global diversification strategy and corporate profit performance - Chan Kim, W.; Hwang, Peter; Burgers, William P. (Strategic Management Journal, 1989)
Abstract Based on a sample of 62 multinationals, this paper examines the impact of global diversification strategy on corporate profit performance by integrating the product and the international market dimensions of diversification. The results suggest that the corporate profit performance impact of related and unrelated diversification varies contingent upon the extent of a firm's international market diversification. One important lesson of this work is that both business strategy researchers and managers should review corporate diversification as having distinct yet interactive strategic dimensions—product and international market—and they would do well to recognize both the different and the joint effect of these dimensions on corporate profit performance.